2012
DOI: 10.1242/dev.077297
|View full text |Cite
|
Sign up to set email alerts
|

MLCK regulates Schwann cell cytoskeletal organization, differentiation and myelination

Abstract: SummarySignaling through cyclic AMP (cAMP) has been implicated in the regulation of Schwann cell (SC) proliferation and differentiation. In quiescent SCs, elevation of cAMP promotes the expression of proteins associated with myelination such as Krox-20 and P0, and downregulation of markers associated with the non-myelinating SC phenotype. We have previously shown that the motor protein myosin II is required for the establishment of normal SC-axon interactions, differentiation and myelination, however, the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
(54 reference statements)
1
7
0
Order By: Relevance
“…Alpha‐Parvin‐deficient vascular smooth muscle cells fail to polarize their cytoskeleton, resulting in loss of persistent and directed migration (Montanez et al, ). Another study showed that knockdown of MLCK in Schwann cells induced plasma membrane expansion (Leitman et al, ). In this study, we detected the up‐regulation of the MLCP gene (PPP1R12A gene) and down‐regulation of the MLCK gene (MYLK gene).…”
Section: Discussionmentioning
confidence: 99%
“…Alpha‐Parvin‐deficient vascular smooth muscle cells fail to polarize their cytoskeleton, resulting in loss of persistent and directed migration (Montanez et al, ). Another study showed that knockdown of MLCK in Schwann cells induced plasma membrane expansion (Leitman et al, ). In this study, we detected the up‐regulation of the MLCP gene (PPP1R12A gene) and down‐regulation of the MLCK gene (MYLK gene).…”
Section: Discussionmentioning
confidence: 99%
“…They depend on laminin/integrin β1 interactions (Feltri et al, 2002), downstream activation of the small RhoGTPase Rac1 (Benninger et al, 2007;Nodari et al, 2007) via lymphoid cell kinase phosphorylation (Ness et al, 2013), and regulation of its targets N-WASP (Jin et al, 2011;Novak et al, 2011) and MLCK/myosin II (Wang et al, 2008;Leitman et al, 2011). Together with the negative regulation of Rho/ROCK signaling by Ilk (Pereira et al, 2009), they control SC cytoskeleton reorganization and the formation of SC lamellipodia largely through not yet fully characterized downstream targets and functional mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…6). Such pathways control several cytoskeleton modulators, including N-WASP (Tomasevic et al, 2007;Jin et al, 2011;Novak et al, 2011) and MLCK/myosin II (Wang et al, 2008;Leitman et al, 2011), that are key in regulating radial lamellipodia formation, an essential requirement for radial sorting and axon ensheathing. Although Rac1 is a positive regulator, promoting radial lamellipodia and radial sorting, Rho/ROCK can counteract it as a negative regulator, repressing their formation.…”
Section: Pfn1 Regulates Sc Radial Lamellipodia Independently Of Rac1mentioning
confidence: 99%
See 2 more Smart Citations